(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The major aim of this study is to ascertain the feasibility of using recycled products in form of post- consumer material using different regrind ratios to produce new products without a significant reduction in product quality. Four regrind ratios were used in this study: 0%, 20%, 50% and 100%. The used products were collected from different public places in Benghazi city-Libya. The properties under investigation are: mass, shrinkage, colour and solid density. The results indicated to no remarkable change in the concerned properties.